Common bean seed germination and seedling emergence under inoculation with biostimulators - Solino, Antônio Jussiê da Silva; Oliveira, Juliana Santos Batista de; Schmitt, Maycon; Silva, Jéssica Brasau da; Schwan-Estrada, Kátia Regina Freitas (Scientia Agraria Paranaensis, 2020)
Biostimulating microorganisms have protector effect against pathogenic agents, affect the stand formation, promote plant growth, and increase yield of agricultural crops. Thus, the objective of this work was to evaluate the seed germination and seedling emergence of different common bean cultivars as a function of treatments with Bacillus subtilis BV02 and Trichoderma asperellum BV10. Germination tests in paper rolls and sand were conducted in a completely randomized design, with a 2×4 factorial arrangement consisted of two cultivars, namely Campos Gerais (CG) and Estilo (ES), and four microorganism treatments, namely B. subtilis BV02 (BS), T. asperellum BV10 (TA), B. subtilis BV02 + T. asperellum BV10 (BS+TA), and Control. The variables analyzed were: germination speed index (GSI), emergence speed index (ESI), germination percentage, emergence percentage, root length, seedling height, and root and shoot fresh and dry weights. The CG cultivar had higher GSI, ESI, root length, seedling height, shoot fresh weight, root fresh weight, and shoot dry weight than the ES cultivar in the paper roll and sand tests. The common bean seed inoculation with BS+TA increased seedling height, shoot fresh weight, shoot dry weight, and root length in the ES cultivar. The CG cultivar had higher GSI, ESI, root length, root fresh weight, and root and shoot dry weights than the ES cultivar. The treatment of seeds with BS+TA is recommended to improve the performance of common bean seedlings of the ES cultivar.